The effect of giving NaOCL 2.5% and H2O2% solution on the initial setting Mineral Trioxide Aggregate (MTA) - Wardhani, Saraswati Dian; Usman, Munyati; Kamizar, K. (Padjadjaran Journal of Dentistry, 2009)
Today, Mineral Trioxide Aggregate (MTA) is one of the most commonly-used materials to overcome problems in dental pulp as well as periodontal tissue. This substance received its permission from the American Food and Drug Administration (FDA) in 1998 and has been patented as a Portland type I.ASTM C150 cement-base material. However, MTA still has its flaws, such as: its granule form, requirement for moist condition, mass losing during hydration (high solubility), and particularly its time-consuming setting duration (45’-165’). Some researches attempt the usage of regular accelerator together with Portland cement, yet there’s still no certainty of the best concentration that can be used to gain optimal result. This research conducted a time test of the initial setting of MTA that was mixed with the strong-oxidation antimicrobial solutions, they are NaOCl 2.5% dan H2O2 3%. The instrument used was the Gillmore needle. Data analysis used one-way ANOVA and Mann Whitney significance test (p<0,05). The result of the research showed that the mixing of NaOCl 2.5% with MTA the initial setting was ± 11 minutes and the mixing of NaOCl 2.5% with MTA the initial setting was ± 5 minute, it compared with the initial setting of original MTA which was the initial setting ± 50 minutes.